Geodynamics and Seismic Hazard in the Lasithi Region (EastCrete, Greece) - Kaviris, G.; Voulgaris, N.; Lozios, S.; Soukis, K.; Zymvragakis, A; Vassilakis, E; Antoniou, V. (37th General Assembly (GA) of the European Seismological Commission, 2021)
Lasithi is the easternmost regional unit on Crete Island (Greece), south of which lies the Hellenic Arc. The broader offshore study area is dominated by reverse and strike-slip faulting, while active normal faults are mapped on land. Detailed research of the latter suggests that the northern and central parts of Lasithi are affected by arc-parallel extension, whereas the southern part by arc-normal extension. The NNE-SSW striking faults are more frequent and form horst and graben or half-graben macro-structures. These faults usually consist of two or more segments accompanied by post-glacial scarps and clear evidence of recent reactivations. The E-W to ESE-WNW striking faults are scarcer and mainly observed along the southern coastal zone or offshore. Compared to the NNE-SSW strikingfaults, they present fewer active traces. Significant events in the study area include the 8th August1303 (M≈8.0) earthquake and the 1st July 2009 (Mw=6.4) earthquake that occurred south of Crete, triggering a small tsunami. A probabilistic seismic hazard assessment is performed for Lasithi. The maximum expected ground motion parameters (PGA, PGV and PGD) for mean return periods of 475and 950 years are determined using the SHARE 2013 zones and seismicity model. Greek GMPEs that consider type of faulting and soil type were applied. Optimum results are obtained through a logic-tree approach, which considers all GMPEs. The Uniform Hazard Spectrum for Agios Nikolaos, Sitia and Ierapetra are presented and compared with the elastic design spectra proposed by the Greek National Building Code and Eurocode 8.